O poder legislativo na verificação da legitimidade constitucional do processo de construção das leis - Fontes, Washington Alves de (2009)
It is known that, in the Democratic State of Law paradigm, one of the most instigating themes is the legitimity of the Law. It justifies the interest in reflecting about the Legislative Process instituted by the Brasilian 1988 Constitution, more specifically field of the constitutionality control as away to guaranty of the legitimity of the Law. The research that is developed here, intents to bring to reflection the basis and the ways the Legislative Power has to proceed to Constitutionality Control of the laws and of the Legislative Process. As the focus taken here is about the Legislative Power, it starts from the presupposed that only by the adoption of legislative process which has to be connected to a rational speech, that will evidence the Democratic and Procedimental Law dimensions, guarantee the possibility of the public and private spheres of life act in complementarity that is such needed to the stabilization of the social expectatives and the concretization of the Brazilian Constitution